Total Quality Management (TQM): Sebuah Langkah dalam Mengedepankan Kualitas Output melalui Sistem Kontrol Mutu (Quality Control) Sekolah - Aminatul Zahroh; Binti Maunah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
Total Quality Management (TQM) is an attempt to maximize competitiveness through continuous improvementÂ process in this case the school is able to recognize the capabilities, advantages and also disadvantages.Â Implementation of Total Quality Management (TQM) in achieving quality education supported by high qualityÂ / quality output at the school is to improve all aspects of both the completeness of infrastructure facilities,Â the professionalism of teachers, as well as the quality of graduates (output). The purpose of this study was toÂ determine the performance of Total Quality Management in achieving quality output through quality controlÂ (quality control) school. In the implementation of quality control is required a shared commitment among allÂ components in the school, between school leaders, teachers, students, other school staff, parents also learners.Â The method used in the writing of this study is literature. Primary data obtained from studies and readingÂ through the books according to subject. The study was conducted at the beginning of September 2014, involvingÂ discussions among peers. Based on these discussions concluded that: 1) Build quality so that it becomes a qualityÂ output needed a shared commitment among all components in the school, between school leaders, teachers,Â students, other school staff, parents also learners. 2) To get the quality of quality, to provide education notÂ only give priority to the supply of input factors, but also the process. The quality of education can be fulfilled ifÂ there is an increase in the quality of school management with regard elements of input, process and output. 3)Â Total Quality Management (TQM) through a system of quality control (quality control) is an approach whichÂ seeks to improve the quality of education through the process so that it becomes a quality output, quality, andÂ competitiveness. Improvement of the quality of the output is not only a school program, but also a governmentÂ program.